Answer:
![y(t)=2e^{3t}(2-5t)](https://tex.z-dn.net/?f=y%28t%29%3D2e%5E%7B3t%7D%282-5t%29)
Step-by-step explanation:
Let Y(s) be the Laplace transform Y=L{y(t)} of y(t)
Applying the Laplace transform to both sides of the differential equation and using the linearity of the transform, we get
L{y'' - 6y' + 9y} = L{0} = 0
(*) L{y''} - 6L{y'} + 9L{y} = 0 ; y(0)=4, y′(0)=2
Using the theorem of the Laplace transform for derivatives, we know that:
![\large\bf L\left\{y''\right\}=s^2Y(s)-sy(0)-y'(0)\\\\L\left\{y'\right\}=sY(s)-y(0)](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20L%5Cleft%5C%7By%27%27%5Cright%5C%7D%3Ds%5E2Y%28s%29-sy%280%29-y%27%280%29%5C%5C%5C%5CL%5Cleft%5C%7By%27%5Cright%5C%7D%3DsY%28s%29-y%280%29)
Replacing the initial values y(0)=4, y′(0)=2 we obtain
![\large\bf L\left\{y''\right\}=s^2Y(s)-4s-2\\\\L\left\{y'\right\}=sY(s)-4](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20L%5Cleft%5C%7By%27%27%5Cright%5C%7D%3Ds%5E2Y%28s%29-4s-2%5C%5C%5C%5CL%5Cleft%5C%7By%27%5Cright%5C%7D%3DsY%28s%29-4)
and our differential equation (*) gets transformed in the algebraic equation
![\large\bf s^2Y(s)-4s-2-6(sY(s)-4)+9Y(s)=0](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20s%5E2Y%28s%29-4s-2-6%28sY%28s%29-4%29%2B9Y%28s%29%3D0)
Solving for Y(s) we get
![\large\bf s^2Y(s)-4s-2-6(sY(s)-4)+9Y(s)=0\Rightarrow (s^2-6s+9)Y(s)-4s+22=0\Rightarrow\\\\\Rightarrow Y(s)=\frac{4s-22}{s^2-6s+9}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20s%5E2Y%28s%29-4s-2-6%28sY%28s%29-4%29%2B9Y%28s%29%3D0%5CRightarrow%20%28s%5E2-6s%2B9%29Y%28s%29-4s%2B22%3D0%5CRightarrow%5C%5C%5C%5C%5CRightarrow%20Y%28s%29%3D%5Cfrac%7B4s-22%7D%7Bs%5E2-6s%2B9%7D)
Now, we brake down the rational expression of Y(s) into partial fractions
![\large\bf \frac{4s-22}{s^2-6s+9}=\frac{4s-22}{(s-3)^2}=\frac{A}{s-3}+\frac{B}{(s-3)^2}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20%5Cfrac%7B4s-22%7D%7Bs%5E2-6s%2B9%7D%3D%5Cfrac%7B4s-22%7D%7B%28s-3%29%5E2%7D%3D%5Cfrac%7BA%7D%7Bs-3%7D%2B%5Cfrac%7BB%7D%7B%28s-3%29%5E2%7D)
The numerator of the addition at the right must be equal to 4s-22, so
A(s - 3) + B = 4s - 22
As - 3A + B = 4s - 22
we deduct from here
A = 4 and -3A + B = -22, so
A = 4 and B = -22 + 12 = -10
It means that
![\large\bf \frac{4s-22}{s^2-6s+9}=\frac{4}{s-3}-\frac{10}{(s-3)^2}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20%5Cfrac%7B4s-22%7D%7Bs%5E2-6s%2B9%7D%3D%5Cfrac%7B4%7D%7Bs-3%7D-%5Cfrac%7B10%7D%7B%28s-3%29%5E2%7D)
and
![\large\bf Y(s)=\frac{4}{s-3}-\frac{10}{(s-3)^2}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20Y%28s%29%3D%5Cfrac%7B4%7D%7Bs-3%7D-%5Cfrac%7B10%7D%7B%28s-3%29%5E2%7D)
By taking the inverse Laplace transform on both sides and using the linearity of the inverse:
![\large\bf y(t)=L^{-1}\left\{Y(s)\right\}=4L^{-1}\left\{\frac{1}{s-3}\right\}-10L^{-1}\left\{\frac{1}{(s-3)^2}\right\}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20y%28t%29%3DL%5E%7B-1%7D%5Cleft%5C%7BY%28s%29%5Cright%5C%7D%3D4L%5E%7B-1%7D%5Cleft%5C%7B%5Cfrac%7B1%7D%7Bs-3%7D%5Cright%5C%7D-10L%5E%7B-1%7D%5Cleft%5C%7B%5Cfrac%7B1%7D%7B%28s-3%29%5E2%7D%5Cright%5C%7D)
we know that
![\large\bf L^{-1}\left\{\frac{1}{s-3}\right\}=e^{3t}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20L%5E%7B-1%7D%5Cleft%5C%7B%5Cfrac%7B1%7D%7Bs-3%7D%5Cright%5C%7D%3De%5E%7B3t%7D)
and for the first translation property of the inverse Laplace transform
![\large\bf L^{-1}\left\{\frac{1}{(s-3)^2}\right\}=e^{3t}L^{-1}\left\{\frac{1}{s^2}\right\}=e^{3t}t=te^{3t}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20L%5E%7B-1%7D%5Cleft%5C%7B%5Cfrac%7B1%7D%7B%28s-3%29%5E2%7D%5Cright%5C%7D%3De%5E%7B3t%7DL%5E%7B-1%7D%5Cleft%5C%7B%5Cfrac%7B1%7D%7Bs%5E2%7D%5Cright%5C%7D%3De%5E%7B3t%7Dt%3Dte%5E%7B3t%7D)
and the solution of our differential equation is
![\large\bf y(t)=L^{-1}\left\{Y(s)\right\}=4L^{-1}\left\{\frac{1}{s-3}\right\}-10L^{-1}\left\{\frac{1}{(s-3)^2}\right\}=\\\\4e^{3t}-10te^{3t}=2e^{3t}(2-5t)\\\\\boxed{y(t)=2e^{3t}(2-5t)}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%20y%28t%29%3DL%5E%7B-1%7D%5Cleft%5C%7BY%28s%29%5Cright%5C%7D%3D4L%5E%7B-1%7D%5Cleft%5C%7B%5Cfrac%7B1%7D%7Bs-3%7D%5Cright%5C%7D-10L%5E%7B-1%7D%5Cleft%5C%7B%5Cfrac%7B1%7D%7B%28s-3%29%5E2%7D%5Cright%5C%7D%3D%5C%5C%5C%5C4e%5E%7B3t%7D-10te%5E%7B3t%7D%3D2e%5E%7B3t%7D%282-5t%29%5C%5C%5C%5C%5Cboxed%7By%28t%29%3D2e%5E%7B3t%7D%282-5t%29%7D)